Análisis del nivel de satisfacción laboral de los trabajadores de la Dirección Regional de Trabajo y Promoción del Empleo Loreto - oficina Iquitos, periodo febrero 2019 - Iglesias Díaz, Rut Ester (2021)
The Regional Directorate of Labor and Employment Promotion Loreto, is a decentralized entity, with administrative and budgetary dependence of the Regional Government of Loreto and technical and regulatory dependence of the Ministry of Labor and Employment Promotion. The objective of this thesis was to determine the level of job satisfaction of the workers of the Regional Directorate of Labor and Employment Promotion Loreto - Iquitos Office, in the period February 2019; developing for this research Quantitative type, Correlational level and Non-Experimental design. The conclusion of the investigation was that the level of job satisfaction of workers is "Medium" (65.79%), "Yes" workers are working with the work they do (68.42%), they consider the work environment to be " Good ”(65.79%), they are“ Dissatisfied ”with the remuneration they receive for the work carried out (44.74%). When the level of job satisfaction was related to job performance, a statistical fashion of 16 servers was obtained that have a level of satisfaction "Medium" and "Yes" feels done at work. The relationship between the level of satisfaction and the work environment, the statistical fashion was 17 workers, identified with a level of satisfaction "Medium" and with a work climate "Good." Finally, the relationship between the level of satisfaction and satisfaction with the remuneration received has a statistical fashion of 13 people.